2021
DOI: 10.3390/ani11020505
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Velogenic Newcastle Disease Virus (Sub-Genotype VII.1.1) from Wild Birds, with Assessment of Its Pathogenicity in Susceptible Chickens

Abstract: Newcastle disease (ND) is considered to be one of the most economically significant avian viral diseases. It has a worldwide distribution and a continuous diversity of genotypes. Despite its limited zoonotic potential, Newcastle disease virus (NDV) outbreaks in Egypt occur frequently and result in serious economic losses in the poultry industry. In this study, we investigated and characterized NDV in wild cattle egrets and house sparrows. Fifty cattle egrets and fifty house sparrows were collected from the vic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 67 publications
2
29
1
Order By: Relevance
“…These clinical and postmortem observations correlate to disease manifestation findings of birds infected with VNDV in other studies [10,[65][66][67]. However, all examined migratory and non-migratory wild birds that were positive for NDV had no apparent clinical disease signs or post-mortem lesions, which are coherent with the findings recorded in previous studies related to ND infections in wild birds [30,58].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These clinical and postmortem observations correlate to disease manifestation findings of birds infected with VNDV in other studies [10,[65][66][67]. However, all examined migratory and non-migratory wild birds that were positive for NDV had no apparent clinical disease signs or post-mortem lesions, which are coherent with the findings recorded in previous studies related to ND infections in wild birds [30,58].…”
Section: Discussionsupporting
confidence: 90%
“…Conversely, low detection rate of NDV was recorded in wild birds with percentage of 5.18% [50]; 3.06% [47], and 3.77% [29]. In view of a few studies carried out in Egypt on wild bird species, velogenic NDV sub-genotype VII.1.1 was isolated from cattle egret and house sparrows that were collected from the vicinity of poultry farms with a history of NDV infection [30]. Among the 85 samples positive for NDV, the majority 71 (61.6%) contained NDV alone but 14 samples (38.4%) contained both NDV and AIV.…”
Section: Discussionmentioning
confidence: 99%
“…Newcastle disease (ND) is a highly contagious viral disease which infects a wide variety of domestic and wild bird species [ 1 , 2 , 3 ]. The disease produces drastic economic losses worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Velogenic NDV strains can be further subdivided into viscerotropic, which cause severe intestinal and visceral hemorrhages, and neurotropic, which cause severe neurologic clinical signs and encephalitis [ 2 , 16 , 17 , 18 ]. Among poultry, ND has a wide prevalence of infection in over 200 kinds of birds [ 2 , 3 , 19 ]. In many countries, novel genotype VII displayed marked virulence and wide tissue tropism.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the method of detection and differentiation of NDV used in this study, it has been documented that although RT‐PCR and RRT‐PCR cannot replace the virus isolation completely, they are recommended for surveillance programs technique and are useful for rapid screening of at‐risk poultry flocks (Abd‐Elfatah et al., 2021; Camenisch et al., 2008; Wise et al., 2004). The positive cases of waterfowl to Newcastle virus as observed in this study (Table 5) are much higher than previously reported from exotic zoo birds in Tehran (Madadgar et al., 2013) but less than that reported from aquatic birds in Khuzestan province (Talazade & Mayahi, 2013).…”
Section: Discussionmentioning
confidence: 99%